Indicator systems for measuring and monitoring sustainability of transport - Kubáňková, Marie; Hyršlová, Jaroslava; Becková, Helena (Melandrium, 2015)
Transport has significant and long-lasting economic, social and environmental impacts, and so it is an important factor of sustainability. This paper deals with sustainable transport and it is focused primarily on indicator systems for measuring and monitoring transport sustainability. Sustainable transport indicators are defined as statistical measures that give an indication of the sustainability of social, environmental and economic development. The main objective of the paper is to present and clarify frameworks of sustainable transport indicators as results of international research. The paper also explores practical applications of indicators for measuring and monitoring sustainability of transport. Attention is especially paid to the indicators used in the Czech Republic for assessment of individual objectives and measures of the Czech transport policy. The paper provides a basic overview of indicators that are suggested for monitoring and measuring sustainability in the area of transport in comparison with the indicators of the transport policy recommended by the ASSESS project.
Systémy ukazatelů pro měření a monitorování udržitelnosti dopravy
Keywords: sustainability; sustainable transport; sustainable transport indicators; udržitelnost; udržitelná doprava; ukazatele udržitelné dopravy